Nowe spojrzenie na problemy genologii współczesnej. Kryminał Andrieja Kotina = A new look at the problems of contemporary genology. A crime novel of Andriej Kotin - Saja, Krystian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The modern crime novel, as well as other genres, is looking for new aesthetic options. The classic form of crime fiction seems to be insufficient for the ever-growing demands of customers. What is more, a noticeable crisis in the attractiveness of any literature can be observed. This implies the need to combine multiple genres.
Keywords: powieść kryminalna; literatura polska - 21 w. - tematyka; genologia; Kotin, Andrej